Audio description and Australian Television: A position paper - Kent, Michael; Ellis, K.; Locke, K. (Centre for Culture and Technology, 2018)
Audio description (AD) – also referred to as video description, video programming or descriptive video – is a track of narration included between the lines of dialogue which describes important visual elements of a television show, movie or performance. It is an essential feature in order to make television accessible to audiences who are blind or vision impaired. As the human rights of people with disability become more prioritised and expanding technologies allow an individualisation of the experience of television, AD is becoming increasingly available across the world. For example, from its rudimentary beginnings in Spain in the 1940s, to date AD is available through terrestrial broadcast television in the UK, US, Canada, New Zealand, Ireland, Germany, Spain, Italy, Poland, France, Portugal, the Czech Republic, Korea, Thailand, Austria, Switzerland, Belgium and a number of other European countries. However, it is not available on Australian broadcast television, despite the federally funded agency Screen Australia having created a back catalogue of AD content. Screen Australia is the key funding body for the Australian film industry and according to several policy documents requires funded dramas to create an AD track. While producers may create these tracks, there is no mechanism to broadcast them on television. The Australian government and broadcast industry have stated that they believe it to be too technically complicated and financially prohibitive to offer here. This report outlines an AD position paper based on 5 years of research with Australian audiences with disability conducted by researchers in the Department of Internet Studies and the Critical Disability Research Network at Curtin University Australia. The report focuses in particular on the views of Australians with blindness and vision impairments who have taken part in these projects. The report is divided into three sections. Part 1 considers the broader context of the role of television in facilitating social inclusion, including the idea that television access is a fundamental human right. Part 2 considers the ways AD can be delivered, and begins with a brief history of AD, from its beginnings in the middle part of last century to the modern and innovative formats available today. The Big Access Media (BAM) app is presented as an immediate solution, and we argue the industry, especially the public Audio description position paper • page vii broadcaster, the Australian Broadcasting Corporation (ABC), utilise this app to immediately offer AD content to Australians. It will consider how standards, guidelines and legislation have shaped the AD industry worldwide and offer some common guidelines regarding principles, objectivity and voicing. The provision of AD in Australia is also discussed, specifically in relation to a similar accessibility issue – the provision of closed captions. The section concludes by providing case studies on two aspects of Australian media – the two ABC AD trials and the efforts of Screen Australia to increase AD content in this country. While the insights of blind and visually impaired audience members who require AD are featured throughout the report, Part 3 moves on to discuss these observations in more detail. This focuses on feedback from people regarding their access to television which had been carried out in two earlier research projects – this included 13 interview participants with vision impairment and a further 64 who participated in online surveys. Common themes that emerged included: § The importance of the public broadcaster. § Television being a social activity. § The feeling of exclusion – television is considered integral for inclusion. § Issues surrounding cost – the “economics of disability”. § Contradictory approaches to technology – some were willing to try new technology, others preferred older technology and were unwilling to upgrade. § The frustration that Australian content is audio described when exported overseas or released on DVD but is not available on local broadcast television. § Frustration with watching non-AD television content once AD has been experienced. The section concludes by also considering the potential benefits of AD to other audiences, including the elderly, people with intellectual disabilities and people whose first language is not English. The following recommendations are therefore proposed: § AD be made available on Australian free-to-air television either via terrestrial broadcast, catch-up portals or a dedicated app. § Any imported programming with an AD track created for international audiences must be licensed with the AD track for distribution in Australia. Audio description position paper • page viii § Further research is conducted to establish the mainstream benefits of AD and talking electronic programing guides (EPGs). The ways people consume media is constantly changing – if these formats and technologies can be embraced by the mainstream, disability inclusion will improve. § Regulation and standards introduced in the 1990s be brought up to date with the 21st century digital and online television environment: § The Broadcasting Services Act (BSA) 1992 should immediately be expanded to encompass television screened online; § Australian standards should be introduced to ensure set-top boxes can receive and display AD; § The BSA should be expanded to include AD. § The government needs to support people with disability to acquire digital literacy skills. Low income members of this group should also be supported financially to get online. § Innovation and competition in the business sector must be encouraged, for example to develop more apps to facilitate AD. § Screen Australia policy should be expanded to television drama in more explicit terms. § The public broadcasters should be supported to provide AD. § Australian licensing laws be relaxed to allow pubic broadcasters to continue airing shows on their catch-up portals with AD tracks even when they have moved to commercial or subscription channels. § Further audience research into the feasibility of synthetic voice systems be conducted to discover whether this is an acceptable interim or long-term solution to the provision of AD.